Visualisation de données et design émotionnel peuvent-ils se conjuguer? - Tiffany Andry (Communiquer)
The use of web 2.0 and social digital networks encourages the upsurge of data visualization that is often attractive and pleasant to watch. We can therefore see embellishment practices, even if the pioneers of information visualization such as Jacques Bertin and Edward Tufte advocate simplicity and minimalism in graphical representations. Yet cognitive scientist Donald A. Norman talks about the emotional design. According to him, attractive things work better because they stimulate greater pleasure in use. The downside is that his theory concerns material objects. In this context, forty semi-directive interviews were conducted in laboratory experiments, exposing individuals to different types of data visualizations. Their analysis shows that the characteristics of emotional design appear in the participants’ speeches. This article attempts to apply emotional design to data visualization in order to bring more nuances to minimalist precautions in terms of data visualization design.